Fixed Asset Planning and Safeguarding in Regional Asset Management: The Moderating Role of Information Technology Utilization - Masny Anjelina; Wendy Kala Tikupadang (Advances: Jurnal Ekonomi & Bisnis, 2026)
Purpose: This study examines the effects of fixed asset planning and safeguarding on the effectiveness of regional asset management while evaluating the moderating role of information technology utilization. Research Method: Using a quantitative explanatory design, empirical data were gathered via purposive sampling from 95 public officials in Tana Toraja Regency and analyzed using multiple linear regression, specifically Moderated Regression Analysis (MRA). Results and Discussion: The findings revealed that both asset planning and safeguarding significantly enhanced management effectiveness. Information technology utilization strengthened the relationship between planning and effectiveness but showed no significant interaction in the safeguarding pathway. Implications: These insights suggest that local governments should prioritize digital integration during planning phases while independently reinforcing physical security protocols. Originality: This research provides unique empirical evidence regarding the asymmetric capability of digital governance tools across different operational stages of public asset administration.